2007
DOI: 10.1016/j.abb.2007.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative metabolism of lipoamino acids and vanilloids by lipoxygenases and cyclooxygenases

Abstract: The lipoamino acids and endovanilloids have multiple roles in nociception, pain, and inflammation, yet their biological reactivity has not been fully characterized. Cyclooxygenases (COXs) and lipoxygenases (LOs) oxygenate polyunsaturated fatty acids to generate signaling molecules. The ability of COXs and LOs to oxygenate arachidonyl-derived lipoamino acids and vanilloids was investigated. COX-1 and COX-2 were able to minimally metabolize many of these species. However, the lipoamino acids were efficiently oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…2, and K M and V m values for 8,9-EET and ARA can be found in Table 1. The K M s obtained from these experiments for ARA reacting with COX-1 and COX-2 were similar to literature values (independent t test, P > 0.05) (21). Likewise, K M values for 8,9-EET with COX-1 and COX-2 are not significantly different from the ARA K M s, indicating that both substrates have similar affinities for both enzymes.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…2, and K M and V m values for 8,9-EET and ARA can be found in Table 1. The K M s obtained from these experiments for ARA reacting with COX-1 and COX-2 were similar to literature values (independent t test, P > 0.05) (21). Likewise, K M values for 8,9-EET with COX-1 and COX-2 are not significantly different from the ARA K M s, indicating that both substrates have similar affinities for both enzymes.…”
Section: Resultssupporting
confidence: 72%
“…Results are average ± SEM (n = 3 or 4). ARA kinetic values taken from the literature are in parentheses (21). The relatively high rate of 8,9-EET metabolism by COX-1 and COX-2 determined by oxygen consumption (cons.)…”
Section: Resultsmentioning
confidence: 99%
“…NAGly is subject to cyclooxygenase and lipooxygenase metabolism, producing metabolites with unknown functions (Prusakiewicz et al, 2007). However, these metabolites are probably not involved in the T-channel inhibition since similar inhibition was obtained in cell-free outside-out patches.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that N-acylglycines are biosynthetic precursors to the PFAMs using purified PAM [72] and in PAM-expressing neuroblastoma cells [93][73] [92][E1]. Marnett and co-workers have found that the N-arachidonoylamino acids are substrates for lipoxygenase and cyclooxygenase in vitro [94,95], pointing either to a mechanism for the inactivation of the N-arachidonoylamino acids or for the formation of other bioactive, oxidized amino acid conjugates. Clearly, there is much work remaining to better define the pathways of biosynthesis and degradation for the N-acylamino acids.…”
Section: N-acylamino Acidsmentioning
confidence: 99%
“…The most common N-terminal acyl group found in eukaryotes is myristic acid, but other fatty acids, including lauric acid, (cis-Δ 5 )-tetradecaenoic acid (physeteric acid), (cis,cis- The catabolic fates of the N-acylamino acids are not well-defined. FAAH will hydrolyze the N-acyltaurines and N-arachidonoylglycine to the corresponding fatty acid and amino acid [33,76] [94,95], pointing either to a mechanism for the inactivation of the N-arachidonoylamino acids or for the formation of other bioactive, oxidized amino acid conjugates. Clearly, there is much work remaining to better define the pathways of biosynthesis and degradation for the N-acylamino acids.…”
Section: N-acylamino Acidsmentioning
confidence: 99%